2022
DOI: 10.3390/su141610342
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Production of Erythritol from Cane Molasses Using Candida magnoliae: Media Optimization, Purification, and Characterization

Abstract: Erythritol is a natural, zero-calorie sweetener that can be used as a sugar substitute and humectant for different products such as confectionaries, tablets, etc. Methods such as extraction and chemical synthesis for erythritol synthesis are not feasible or sustainable due to lower yield and higher operating costs. In the present study, erythritol is produced through the submerged fermentation of cane molasses, a by-product of the cane sugar industry, in the presence of the osmophilic yeast Candida magnoliae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Research on yeast metabolism and genetic engineering to increase yield and productivity and on the utilization of low-cost substrates is directed to reduce production costs. Recent studies show how Y. lipolytica can utilize pure or crude glycerol for erythritol production [84] and Candida magnoliae is able to assimilate the sucrose content of cane molasses and convert it to erythritol [85].…”
Section: Erythritolmentioning
confidence: 99%
“…Research on yeast metabolism and genetic engineering to increase yield and productivity and on the utilization of low-cost substrates is directed to reduce production costs. Recent studies show how Y. lipolytica can utilize pure or crude glycerol for erythritol production [84] and Candida magnoliae is able to assimilate the sucrose content of cane molasses and convert it to erythritol [85].…”
Section: Erythritolmentioning
confidence: 99%
“…For example, researchers in China have reported that erythritol is produced commercially by fermentation using microorganisms giving high yields, such as Aureobasidium sp., Torula corallina , Candida magnoliae , Moniliella sp., Pseudozyma tsukubaensis , Clavispora lusitaniae and Yarrowia lipolytica (e.g. Eszterbauer & Nemeth, 2022 ; Huang et al., 2023 ; Jeya et al., 2009 ; Khatape et al., 2022 ; Lee et al., 2003 ; Moon et al., 2010 ; Seshadrinathan & Chakraborty, 2022 ; Shukla et al., 2023 ). Alternative fermentation techniques, e.g.…”
Section: Assessmentmentioning
confidence: 99%
“…Significant consumption of erythritol can cause side effects such as abdominal pain and diarrhoea. In addition, erythrol shows health-promoting effects on the body through its antioxidant properties and reducing the risk of developing dental caries, thanks to stopping the fermentation of sugars by the bacteria responsible for the formation of dental cavities [18].…”
Section: Introductionmentioning
confidence: 99%